The Total Mediating Effect of Corruption on the Relationship between the Code of Ethics and Corporate Performance. (c2016) - Bou Zakhem, Najib (2016)
The code of ethics became a demanding concern for every corporation. Taking the case of Lebanon, the law does not require companies to adopt a code of ethics or any similar ethics program. Consequently companies tend to neglect the importance of the code on improving the quality of anti-corruption practices within the firm and the performance of the firm as a whole. The purpose of this study is to examine the nature of the relationships existing among the three factors: code of ethics, perceived corruption, and corporate functioning. The study also aims to address the total mediating effect that perceived corruption plays in the relationship between the code of ethics and corporate performance. This quantitative study uses a questionnaire composed of thirty two questions administered and distributed among managers and employees working within SMEs in Lebanon. The PLS-SEM method using SmartPLS 3 software was implemented to analyze the data. The findings reveal that the direct effect of the code of ethics on performance is non-significant and suggest a strong negative relationship between the code of ethics and perceived corruption as well as between perceived corruption and corporate performance. These results also point out a total mediating effect for perceived corruption on the connection between the code of ethics and corporate performance.